Can Interactions Enhance Student Satisfaction in Online Learning During a Crisis? : An Indonesian Study - Sany, Sany; Sudarjo, Olivia Yuriko (Universitas Pendidikan Ganesha, 2024)
This research aims to examine the effect of internet facility, platform, learner-learner interaction, and learner-instructor interaction on student satisfaction. This quantitative research uses the survey method to collect data by distributing questionnaires through Google Forms. The research sample consisted of 179 students from the Business Accounting, Tax Accounting, and International Business Accounting major batch of 2017–2021 at Petra Christian University Indonesia. The data was analyzed using SPSS software by testing statistic descriptive, reliability, validity, and multiple regression. The results show that internet facilities and learner-instructor interaction have a significant positive effect on student satisfaction during online learning, while the platform and learner-learner interaction have not impact on student satisfaction during online learning when the COVID-19 pandemic occurred.